Efficacy of a Thai Herbal Remedy in Patients with Mild Chronic Plaque Psoriasis: An Observer-Blinded Randomized, Standard Treatment-Controlled Trial - Chankeaw K. (2023)
Background: Psoriasis is a chronic non-infectious inflammatory skin disease caused by genetic and environmental predispositions. There is a Thai herbal remedy for psoriasis recorded in Wat Pho’s marble inscriptions, consisting of Dictyophora indusiate Fisch, Psilocybe cubensis (Earle) Sing, and sesame oil. Objective: To compare the efficacy and safety of a Thai herbal remedy as an alternative treatment to the standard treatment of 0.1% triamcinolone lotion in patients with mild chronic plaque psoriasis. Materials and Methods: A randomized, split-body controlled design was conducted in 30 mild chronic plaque-type psoriasis patients with symmetrically distributed psoriasis rashes. Each patient was randomized to apply a Thai herbal remedy on a rash on one side of the body and 0.1% triamcinolone lotion on the other side, using the same dosage of twice daily for eight weeks. Efficacy was assessed at week 1, 2, 4, and 8 by the Targeted Area Score (TAS). The Self-Assessment Score (SAS) at week 8 was compared to the baseline. Safety was assessed through the interviews at each visit. Product satisfaction was evaluated by the visual analog scale (VAS). Results: The TAS and SAS for erythema, desquamation, and induration decreased in both treatment groups, with no significant difference. However, product satisfaction in color (p=0.012), odor (p=0.013), and absorption (p=0.003) were significantly higher in the 0.1% triamcinolone lotion group. Conclusion: The present study showed that the Thai herbal remedy was safe and efficacious in treating chronic plaque-type psoriasis, therefore, can be used as an alternative treatment.